The Rural Past-in-Present and Postwar Sub/urban Progress - Denton, Stacy (American Studies, 2018)
The suburban ideal of the postwar (mid-1940s-late 1960s) U.S., like other eras of suburban development, has been widely studied as a reflection of the fears, desires and aspirations of its society. In addition to reflecting the upward mobility towards which many members of the postwar aspired, the suburban ideal has also been seen as reflecting a desire for the middle-class (and specifically, the white middle-class) to mainstain a distance from the racial minorities still living in the inner-city. Not included in such analyses are other groups of Americans from whom postwar suburbanites also attempted to maintain their distance as they sought out the suburban dream: the working-class and working poor, particularly those people associated with the rural spaces into which the suburbs were built. A look at postwar discourse in the social sciences and popular journalism illustrates the attempt to distinguish between the middle-class moving outside of the cities and the seemingly low-class rural residents who already lived in such places. In highlighting the perceived differences between the middle-class suburbanites and low-class rural residents, such discussions called upon the larger postwar attitude towards rurality as a regressed location, left behind a "modern" society figured as middle-classed and sub/urban. Rurality in the postwar was simultaneously idealized through a nostalgic lens and devalued as the province of the most retrograde members of society, considered a mere backdrop against which the postwar forged ahead.  The intersection of class and geography in postwar discourse was thus used to centralize the markers of postwar progress associated with middle-classed sub/urban development, while overwriting those places and people – including the rural, white working-class – that fell outside such appearances.